Comprehensive Gene Expression Analysis in NMIBC Using RNA-seq Reveals New Therapy Strategies - Chen, Xiaoliang; Jiang, Fuquan; Jia, Chunshu; Liu, Ming; Nan, Yonghao; Qu, Licheng; Kong, Qingkuo; Hou, Fangfang; Luo, Wenshan; Na, Wanli; Jin, Xuefei; Tan, Jiufeng (Frontiers in Oncology, 2019)
Non-muscle invasive bladder cancer (NMIBC) patients often have fewer treatment options, and suffer the progression of disease due to mechanisms that are not clear, as well as due to its diversity. This study was designed to explore the molecular mechanism of bladder cancer through an RNA-seq. In addition to conventional analyses, we also simplified the network through modularization using the WGCNA algorithm, with the help of the topological overlapping matrix and hierarchical cluster tree, which are based on the PPI network of STRING. Furthermore, the hub genes were confirmed through survival analyses in the independent cohorts (n = 431). Among them, 15 genes were significantly associated with poor prognosis. Finally, we validated the results at mRNA and protein level using qRT-PCR, IHC and western blotting. Taken together, our research is important for the prediction, as well as the prospective clinical development of drug targets and biomarkers.